Indoor air quality assessment of elementary schools in Curitiba, Brazil - Godoi, R. H M; Avigo, D.; Campos, V. P.; Tavares, T. M.; Marchi, Mary Rosa Rodrigues de [UNESP]; van Grieken, R.; Godoi, A. F L (Springer Nature, 2009)
The promotion of good indoor air quality in schools is of particular public concern for two main reasons: (1) school-age children spend at least 30% of their time inside classrooms and (2) indoor air quality in urban areas is substantially influenced by the outdoor pollutants, exposing tenants to potentially toxic substances. Two schools in Curitiba, Brazil, were selected to characterize the gaseous compounds indoor and outdoor of the classrooms. The concentrations of benzene, toluene, ethylbenzene, and the isomers xylenes (BTEX); NO2; SO2; O3; acetic acid (HAc); and formic acid (HFor) were assessed using passive diffusion tubes. BTEX were analyzed by gas chromatography-ion trap mass spectrometry and other collected gasses by ion chromatography. The concentration of NO2 varied between 9.5 and 23 μg m-3, whereas SO2 showed an interval from 0.1 to 4.8 μg m-3. Within the schools, BTEX concentrations were predominant. Formic and acetic acids inside the classrooms revealed intermediate concentrations of 1.5 μg m-3 and 1.2 μg m-3, respectively. © Springer Science + Business Media B.V. 2009.
Keywords: Aldehydes; BTEX; Elementary schools; Indoor air quality; air quality; aldehyde; atmospheric pollution; environmental assessment; gas chromatography; indoor air; mass spectrometry; pollution exposure; primary education; sulfur dioxide; toxic substance; urban area; Brazil; Curitiba; Parana